Eventyret Antarktis - Børde, Haakon; Johansen, Karl Hans (Gyldendal, 1978)
Keywords: Antarktis; Norge; Norsk Polarinstitutt; Sydpolsekspedisjonen; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

An eruptional model for recent lava flow on Bouvetøya, South Atlantic Ocean - Furnes, Harald; Løvlie, Reidar (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; geologi

Age relationships of Mesozoic basalt lava and dykes in Vestfjella, Dronning Maud Land, Antarctica - Furnes, Harald; Mitchell, John G (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geokjemi; geologi; petrografi; vulkaner

Stratigraphy and igneous petrology of Southern Heritage Range, Ellsworth Mountains, Antarctica - Hjelle, Audun; Ohta, Yoshihide; Winsnes, Thore S (Results from Norwegian Antarctic Research 1974-1977, 1978)
Sedimentary and magmatic rocks of Late Proterozoic to Late Paleozoic age, from the southern half of Ellsworth Mountains are described. Basic volcanic rocks, mainly agglomeratic, occur abundantly in the lower part of the succession, in the Minaret Group, and in the lower part of the Heritage Group, but are not recorded in the upper part of the Heritage Group. Due to this lithostratigraphic contrast a new classification is proposed: the Heritage Group including the Middle Horseshoe Formation and the Edson Hills Formation. A stratigraphic gap is evident above the Edson Hills Formation and a separate unit--the Dunbar Ridge Formation--is proposed. This formation is of Middle-Upper Cambrian age, with trilobite-bearing limestones. The structure is governed by a major anticline with a NW plunge in the north but almost horizontal in the south. Contrast of fold intensity and fold style below the youngest exposed unit, the Whiteout Conglomerate and a weathered surface above the Crashite Quartzite suggests a late Paleozoic deformation phase. Two phases of magmatism are distinguished. The pre-Middle Cambrian magmatism is dominantly K-alkalic and suggests the beginning of block subsidence at the early stage of a rift tectonics on a continental crust. The presumptive Late Paleozoic magmatism is N-alkalic and tholeiitic, and occurred after the main deformation; however the rocks were regionally metamorphosed in the actinolite-greenschist facies probably in late Paleozoic time. This magmatism is considered to represent an advanced stage of block tectonics. (Auth. mod.)
Keywords: Antarktis; ekspedisjoner; geologi; petrologi; stratigrafi; vulkaner

Den norske Antarktis-ekspedisjonen 1976/77 - Orheim, Olav (Naturen, 1978)
Keywords: Antarktis; ekspedisjoner; forskning

Snow accumulation and snow stratigraphy on Riiser-Larsenisen, Dronning Maud Land, Antarctica - Repp, Kjell (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; glasiologi; isshelf; snø; stratigrafi

Weather and tide observations at Bouvetøya - Vinje, Torgny E (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi; observasjoner; oseanografi

Observations on birds and seals at Bouvetøya - Fevolden, Svein Erik; Sømme, Lauritz (Norsk Polarinstitutt. Årbok 1976, 1977)
Keywords: Bouvetøya; ekspedisjoner; fugler; pingviner; zoologi

Sydpolen - Mountfield, David; Sollie, Finn (De store polaroppdagelser, 1977)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

The biogeography of some marine planktonic diatoms - Hasle, Grethe Rytter (Deep Sea Research and Oceanographic Abstracts, 1976)
Keywords: Sørishavet; biogeografi; ekspedisjoner; forskning; fytoplankton; marinbiologi; plankton; planteplankton

Med Amundsen til Sudpolen. Dagbokblad - Bjaaland, Olav (Syn og segn, 1975)
Keywords: Antarktis; Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; polarområdene

Fra tjuagutt til sydpolfarer - Gran, Tryggve (Mortensen, 1974)
Keywords: Antarktis; biografi; ekspedisjoner; historie

Some observations on the geology of H. U. Sverdrupfjella, Dronning Maud Land - Hjelle, Audun (Norsk Polarinstitutt. Årbok 1972, 1974)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; stratigrafi

Mass transport of Jutulstraumen ice stream in Dronning Maud Land - Gjessing, Yngvar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; ekspedisjoner; glasiologi; isbreer; isstrøm

A 200-Year Record of Glacier Mass Balance at Deception Island, Southwest Atlantic Ocean, and Its Bearing on Models of Global Climatic Change - Orheim, Olav (The Ohio State University, 1972)
Keywords: Antarktis; ekspedisjoner; glasiologi; isbreer; klimaendringer; meteorologi; storbreen; stratigrafi

Enorme rikdommer skjult i norsk Antarktis? - Fisksdal, Jan (Nå, 1971)
Keywords: Dronning Maud Land; ekspedisjoner; geologi; mineraler; ressurser

The 2nd tropopause : a statistical and physical study - Harsson, Bjørn Geirr (Norsk Polarinstitutt. Skrifter, 1971)
Keywords: Antarktis; Den Norske Antarktisekspedisjonen 1956-60; Det internasjonale geofysiske år 1957-58; IGY 1957-58; atmosfæren; ekspedisjoner; forskning; meteorologi; observasjoner

Kappløpet mot Sydpolen - Jonason, Jan (Tiden, 1971)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene